2015
DOI: 10.1039/c4ob02424a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and immunological studies of N-acyl modified S-linked STn derivatives as anticancer vaccine candidates

Abstract: It is well known that tumor cells express some aberrant glycans, termed tumor-associated carbohydrate antigens (TACAs). TACAs are good targets for the development of carbohydrate-based anticancer vaccines. However, one of the major problems is that carbohydrate antigens possess a weak immunogenicity. To tackle this problem, a number of unnatural N-modified S-linked STn analogues were designed and prepared. Reaction of the modified STn disaccharides with bifunctional adipic acid p-nitrophenyl diester provided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…S Julien found an increased tumorigenicity after transplantation of ST6GalNAc-1 transfected sTn-positive human breast cell line in to mice [ 11 ]. In addition, sTn has also been used as a target for cancer immunotherapy in preclinical and clinical studies [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…S Julien found an increased tumorigenicity after transplantation of ST6GalNAc-1 transfected sTn-positive human breast cell line in to mice [ 11 ]. In addition, sTn has also been used as a target for cancer immunotherapy in preclinical and clinical studies [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the evoked cross‐reactive antibodies did not increase when compared with the native ones . Our group also synthesized and evaluated some S ‐linked STn glycoconjugates, and the experimental results demonstrated that the modified glycoconjugates could stimulate the induction of cross‐reactive IgG antibodies …”
Section: Advances In Tacas Based Cancer Vaccinesmentioning
confidence: 97%
“…195 Our group also synthesized and evaluated some S-linked STn glycoconjugates, and the experimental results demonstrated that the modified glycoconjugates could stimulate the induction of cross-reactive IgG antibodies. 196,197 Hoffmann-Röder and co-workers modified the TF antigen by fluorine substituting the hydroxyl groups, and conjugated the antigen derivatives to TT. The constructed vaccines evoked immune responses.…”
Section: Cross-reactivity-based Cancer Vaccinesmentioning
confidence: 99%
“…[19,20] Despite the almost universal use of b-sialyl chloride [12,21] fort he synthesis of a-S-sialosides, use of this reagent is often complicated by the competing elimination reaction. [21,23] It should be noted that the synthesis of 2-mercapto-Neu5Acd erivatives suffers from unsatisfactory yields because of competing reactions such as elimination and disulfide bond formation under the experimental conditions, [22] whichf urther complicates the formation of the desired thioglycosides.R ecently,amore-reactive cyclic N-acetyl-N5,O4-oxazolidinone-pro-tected sialyl donor with ad ibutyl phosphate anomericl eaving group has been introduced for the synthesis of a-S-sialosides, which eliminates some of these limitations. [21,23] It should be noted that the synthesis of 2-mercapto-Neu5Acd erivatives suffers from unsatisfactory yields because of competing reactions such as elimination and disulfide bond formation under the experimental conditions, [22] whichf urther complicates the formation of the desired thioglycosides.R ecently,amore-reactive cyclic N-acetyl-N5,O4-oxazolidinone-pro-tected sialyl donor with ad ibutyl phosphate anomericl eaving group has been introduced for the synthesis of a-S-sialosides, which eliminates some of these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Amongo therr eported approaches, anomeric S-alkylation has been investigated for the synthesis of a-S-sialosides via generation of af ree sulfhydryl group at the anomeric position in situ. [21,23] It should be noted that the synthesis of 2-mercapto-Neu5Acd erivatives suffers from unsatisfactory yields because of competing reactions such as elimination and disulfide bond formation under the experimental conditions, [22] whichf urther complicates the formation of the desired thioglycosides.R ecently,amore-reactive cyclic N-acetyl-N5,O4-oxazolidinone-pro-tected sialyl donor with ad ibutyl phosphate anomericl eaving group has been introduced for the synthesis of a-S-sialosides, which eliminates some of these limitations. [24] Previously,w er eported the use of sialyl disulfides as nucleophilic donors for the exclusive formation of S-linked a(2!9) disialyll inkages.…”
Section: Introductionmentioning
confidence: 99%